2021
DOI: 10.3390/app11135938
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Floor Layering on Airborne Sound Insulation and Impact Noise Reduction: A Study on Cross Laminated Timber (CLT) Structures

Abstract: The use of timber constructions recently increased. In particular, Cross Laminated Timber floors are often used in multi-story buildings. The development of standardization processes, product testing, design of details and joints, the speed of construction, and the advantages of eco-sustainability are the main reasons why these structures play a paramount role on the international building scene. However, for further developments, it is essential to investigate sound insulation properties, in order to meet the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
(28 reference statements)
3
12
0
Order By: Relevance
“…The eco-friendly properties of wood as a building material and its structural properties have made CLT a promising material for sustainable buildings [6,7]. This happens because the wood for CLT is renewable and has a considerably lower carbon footprint than concrete [6,8]. The CLT components can be produced with extended prefabrication, implying design flexibility and high protection from moisture, and provide great thermal performance [3,6,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eco-friendly properties of wood as a building material and its structural properties have made CLT a promising material for sustainable buildings [6,7]. This happens because the wood for CLT is renewable and has a considerably lower carbon footprint than concrete [6,8]. The CLT components can be produced with extended prefabrication, implying design flexibility and high protection from moisture, and provide great thermal performance [3,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, limited measurement data for sound insulation of massive CLT floors have been published and no reliable prediction models for sound transmission in CLT structures have been found [2,3,5,10,25]. Although several approaches for modeling sound insulation of CLT floors have been developed, including analytical models [8,11,26], finite element methods [4,21,27,28], wave propagation modeling [26], statistical energy analysis [25], and modeling with neural networks [29], to estimate the acoustic performance of CLT floors, acousticians still rely on field or laboratory measurements, which still provide only indications [3,8,10,21].…”
Section: Introductionmentioning
confidence: 99%
“…Timber has been widely and continuously used in construction engineering as it is available in nature and easy to handle [1]. In addition, it has a significantly lower carbon footprint than concrete and provides good thermal performance [2,3]. Wooden buildings have become widely popular in Scandinavia and Australia due to their advantages [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Even though floating floors represent a key method for reducing impact noise, suspended ceilings or structural discontinuities can be utilized to improve the impact sound insulation performance [12,13]. A few studies examined the impact sound insulation performance of suspended ceilings at the bottom parts of floor structures [14][15][16][17][18][19][20][21]. In these studies, the effects of the suspended ceilings on the impact sound insulation performance varied depending on the experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These results were obtained from a suspended ceiling installed at the bottom of the floating floor structures. Bettarello et al [17] showed the influence on impact noise reduction by the floating floor and suspended ceiling on a building featuring a Cross Laminated Timber floor. The findings indicated that impact noise reductions offered by the suspended ceiling and floating floor were very similar for the tapping machine, while the suspended ceiling acted better than the floating floor for the ISO rubber ball, especially at low frequencies.…”
Section: Introductionmentioning
confidence: 99%